Experiential Learning Theory (ELT) dan Implementasinya pada Mata Pelajaran IPA Tema Sumber Energi - Fuad Fitriawan; Lisa Andriani (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study wanted to identify the level of understanding ability, explain the level of understanding, explain the achievements and test the effect of science subjects using the experiential learning method. The material raised in this study is the theme of energy sources, while the subjects of this research are grade IV students at MIN 9 Magetan for the 2021/2022 academic year. The results of this study were analyzed using multiple regression analysis with the final conclusion that students' ability to understand natural science in the energy sources chapter through the experiential learning method obtained a score range of 45-49 as much as 36.7%. The range of values ​​51 – 55 is 63.3%. Then the level of understanding of students obtained a range of values ​​45-48 as much as 23.3%, a range of values ​​49-52 as much as 46.7%, and a range of values ​​53-56 as much as 30%. The achievement of student learning outcomes obtained by the range of values ​​60-80 number 11 was 36.7%, the range of values ​​81-100 was 63.3%, and there was an influence between experiential learning on the ability to understand and its achievements in the science subject chapter on energy sources in class students IV at MIN 9 Magetan with a variable regression coefficient X with Y1 of 0.3999, Tcount = 2.268 and sig. 0.031 < probability 0.05 and the regression coefficient of variable X with Y2 of 3.417, Tcount = 7.438 and sig. 0.000 < probability 0.05.